Amoxicillin for acute lower respiratory tract infection in primary care: subgroup analysis by bacterial and viral aetiology. (August 2018) - Bruyndonckx, R.; Stuart, B.; Little, P.; Hens, N.; Ieven, M.; Butler, C.C.; Verheij, T.; Goossens, H.; Coenen, S.; ,
Abstract: Objective: We aimed to assess the effects of amoxicillin treatment in adult patients presenting to primary care with a lower respiratory tract infection (LRTI) who were infected with a potential bacterial, viral, or mixed bacterial/viral infection. Methods: This multicentre randomized controlled trial focused on adults with LRTI not suspected for pneumonia. Patients were randomized to receive either antibiotic (amoxicillin 1 g) or placebo three times daily for 7 consecutive days using computer-generated random numbers (follow-up 28 days). In this secondary analysis of the trial, symptom duration (primary outcome), symptom severity (scored 0–6), and illness deterioration (reconsultation with new or worsening symptoms, or hospital admission) were analysed in pre-specified subgroups using regression models. Subgroups of interest were patients with a (strictly) bacterial, (strictly) viral, or combined infection, and patients with elevated values of procalcitonin, C-reactive protein, or blood urea nitrogen. Results: 2058 patients (amoxicillin n  = 1036; placebo n  = 1022) were randomized. Treatment did not affect symptom duration ( n  = 1793). Patients from whom a bacterial pathogen only was isolated ( n  = 207) benefited from amoxicillin in that symptom severity ( n  = 804) was reduced by 0.26 points (95% CI −0.48 to −0.03). The odds of illness deterioration ( n  = 2024) was 0.24 (95% CI 0.11 to 0.53) times lower from treatment with amoxicillin when both a bacterial and a viral pathogen were isolated (combined infection; n  = 198). Conclusions: Amoxicillin may reduce the risk of illness deterioration in patients with a combined bacterial and viral infection. We found no clinically meaningful benefit from amoxicillin treatment in other subgroups.